Key elements of toxic myocardiopathy pathogenesis - N. D. Bunyatyan; T. I. Vlasova; N. A. Myshkina; A. P. Vlasov; E. I. Polozova; N. Yu. Leshchankina; A. B. Prokofiev; K. G. Gurevich (Бюллетень сибирской медицины)
Goal. To identify key links in the pathogenesis of toxic myocardiopathy in conditions of endogenous intoxication in peritonitis. Materials and methods. Experimental studies were carried out on dogs (n = 24). The model of purulent fecal peritonitis. We studied the run-time content of toxic products in blood plasma, the lipid composition, the intensity of lipid peroxidation, the activity of phospholipase A2 and superoxide dismutase, and hypoxia of myocardial tissue. We evaluated loss of water and proteins, electrogenesis of the myocardium cells and changes in the ECG parameters. We also performed histological examination of the myocardial tissue. Results. Experimental studies in dogs showed that the development of endotoxicosis of peritoneal origin is accompanied by significant metabolic disorders and cardiac malfunction leading to the development of myocardiopathy. The most important role in the development and progression of myocardial damage in endotoxicosis is played by biomembrane damage and disruption of associated processes. The main processes are quantitative and qualitative modifications of phospholipids in cardiac cell membranes. Conclusion. The obtained data demonstrate the key role of the interrelation between dyslipidemia in the investigated cellular structures and intensification of lipid peroxidation, an increase in phospholipase A 2 activity, and hypoxia; which confirms the significance of these processes in destabilization of the phospholipid matrix of biomembranes.